PERBANDINGAN STRUKTUR DAN KEWENANGAN DPR RI DENGAN DPD RI DALAM FUNGSI LEGISLASI - Suroto Suroto (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2018)
Comparison of structure and authority of DPR RI with DPD RI related to legislation function can be seen from two side, that is philosophical and juridical side. DPR RI with DPD RI from the philosophical side is the incarnation of the representation of the whole people or the representation of the whole area of Indonesia at the central level, from the juridical side of the House of Representatives with DPD RI is a state institution regulated in Article 20 and Article 22D NRI 1945 Constitution. DPR RI with DPD RI related to the function of legislation is the pattern of work relationships that are functional. The constraints faced by the House of Representatives and the DPD RI related to the function of legislation is the Constraints that are institutional and constitutional. Institutional constraints are the obstacles that arise from within the body of the institution between the administrative system of the session, the results of legislation, budget, and supporting system that is less than the maximum, while the constraints are constitutional in terms of regulation of these constraints are often faced by DPD RI, the current arrangement is in Article 22D Paragraph (1) and (2), and the regulation in Law no. 2 Year 2018 About MD3 there is the addition of DPD RI can evaluate the draft law and local regulations (Article 249 J).